The influences of Two Stay-Two Stray (TSTS) technique on students’ reading comprehension - salamun (JEET, Journal of English Education and Technology, 2024)
The aim of this study is to know the influence of Two Stay-Two Stray (TSTS) technique on students’ reading comprehension. Reading is one of essential ways in building students’ knowledge. The researcher uses experimental research which uses two groups, those are experimental group and control group that consist of 46 students. The researcher elaborated the topics that were suitable for narrative text. Finding shows that the students who are taught by using conventional method, it can be proved from the average of speaking achievement. The students who are taught by using two-stay two-stray (76,43) have higher score than those taught by using direct method (68,21). Furthermore, based on the result of T-test, it is shown that sig.(0,002)<0,05. It means that the study indicated Two-stay Two-stray method is effective.